Integration of Character Values in The Islamic Religious Education Curriculum - Muarifah Muarifah; Meti Fatimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research aims to describe the integration of character values in the Islamic Religious Education (PAI) curriculum at MI Miftahul Huda Bonangrejo, Demak, and the implementation process in learning activities. This study employed a descriptive qualitative approach. Data were collected through observation, interviews with PAI teachers and the school principal, and documentation, and analyzed using the Miles and Huberman model. The findings show that five main character values—religiosity, discipline, responsibility, cooperation, and social care—have been systematically integrated into the PAI curriculum. The integration is implemented through thematic learning, teacher role modeling, routine habituation, and strengthening of school culture. These findings are in line with character education theories emphasizing planned and continuous character development. This study is limited to one madrasah and does not examine long-term impacts on students’ character formation. Nevertheless, the results provide practical contributions for improving the implementation of character education in PAI learning at the Madrasah Ibtidaiyah level.